ChemInform Abstract: Construction of Heterocyclic Structures by Trivalent Cerium Salts Promoted Bond Forming Reactions. Issue 17 (28th April 2014) - Properzi, Roberta; Marcantoni, Enrico
Abstract Review: 50 refs.